Human death caused by a giant anteater (Myrmecophaga tridactyla) in Brazil - Haddad, Vidal [UNESP]; Reckziegel, Guilhenne C.; Neto, Domingos G. [UNESP]; Pimentel, Fabio L. (Elsevier B.V., 2014)
The fatal outcome of a defensive attack by a giant anteater (Myrmecophaga tridactyla) is reported. The attack occurred while the victim was hunting, and his dogs cornered the adult anteater, which assumed an erect, threatening position. The hunter did not fire his rifle because of concern about accidentally shooting his dogs. He approached the animal armed with a knife, but was grabbed by its forelimbs. When his sons freed him, he had puncture wounds and severe bleeding in the left inguinal region; he died at the scene. Necroscopic examination showed femoral artery lesions and a large hematoma in the left thigh, with death caused by hypovolemic shock. A similar case is cited, and recommendations are made that boundaries between wildlife and humans be respected, especially when they coinhabit a given area.
Keywords: Anteater; Myrmecophaga; Wild animals; Attacks by wild animals